The PENGARUH MEDIA FLASHCARD DALAM MENINGKATKAN KEMAMPUAN LITERASI MEMBACA ANAK USIA 5-6 TAHUN - Sarwiti, Sarwiti; Sari, Muthia; Ayu Kurniawati, Devi; Sina, Ibnu; Pahrul, Yolanda (Journal of Professional Elementary Education, 2025)
This study investigated the impact of using flashcard media on the reading literacy skills of 5-6-year-old children at RA Asalsabila. Early childhood reading literacy encompasses recognizing letters, sounds, blending letters, and reading syllables and simple words. Using a quantitative method with a quasi-experimental design (pretest-posttest control), this research involved 40 children divided into an experimental group (using flashcards) and a control group (without flashcards). Data was collected through observation and reading tests. The results showed a significant difference between the two groups. The average posttest score of the experimental group dramatically increased from 49.80 to 81.75, while the control group only reached 66.20 (Sig. 2-tailed = 0.000 < 0.05). This proves that flashcards significantly improve reading literacy because their visual, interactive, and multisensory nature attracts children's attention and stimulates their cognition and language. This research contributes to innovations in early childhood education learning and serves as an important reference for educators.